FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI GURU TERHADAP PEMBELAJARAN BERBASIS PROJECT INQUIRY BASED LEARNING DI GUGUS I SDN SOKARAJA - Dedi Kurniawan; Subuh Anggoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the factors affecting teachers perceptions of Project inquiry Based Learning (PJIBL) at Gugus I SDN Sokaraja. The research employed a descriptive qualitative method with a survey approach involving 129 elementary school teacher respondents. The study focused on four main factors: teachers Information and Communication Technology (ICT) skills, teacher self-efficacy, teacher mindset towards PJIBL, and computational thinking skills. The results indicate that teachers ICT skills were categorized as high, with 82% of teachers demonstrating strong ability in utilizing technology during the learning process. Teacher self-efficacy was also found to be very high at 97%, reflecting teachers confidence in implementing PJIBL. The teacher mindset towards PJIBL was categorized as very high 99%, indicating a predominance of a growth mindset supporting the adoption of innovative methods. Meanwhile, computational thinking skills were categorized as high 74%, although some teachers still need to improve their analytical and problem-solving abilities. Overall, these four factors significantly affect teacher perceptions of PJIBL based learning. The findings highlight the importance of these factors in strengthening teachers readiness to face 21st-century learning challenges.